(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Manufacturing medical devices is a complex process that necessitates strict adherence to international standards to ensure quality, safety, and reliability. To enhance competitiveness in both national and global markets, manufacturers can adopt several effective strategies. First and foremost, implementing a robust Quality Management System (QMS) is essential. The ISO 13485 standard provides a comprehensive framework for managing quality. This involves establishing a document control system to ensure that all procedures are current and accessible, monitoring production processes to identify areas for improvement, and conducting regular audits and reviews to facilitate continuous improvement of processes and products